Urgensi Kompetensi Guru Dalam Pelaksanaan Pembelajaran Berbasis Digital Pendidikan - Rina Rahmi; Safrida (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI Miftahul Huda Subang, 2023)
The The rapid development of technology requires teachers to be able to utilize technology in carrying out digital-based learning processes. For this reason, besides having 4 basic skills, teachers are also required to have competence in managing digital-based education. This article aims to examine in more detail the content of teachers and competency standards that will teach teachers and their relation to the digitalization of education. The formulation of the problem in this study is how a teacher is able to balance these competencies with increasingly sophisticated technological developments. This study uses a qualitative approach with a technical analysis of literature related to the digitalization of education. Furthermore, data collection in this study was carried out by tracing various sources, both in the form of government documents, mass media, and the results of relevant research previously analyzed. Data analysis was carried out using content analysis. The results of this study indicate that the competence of a teacher is very necessary because the teacher is an allowance for students in an atmosphere of maximum learning outcomes assisted by the rapid advancement of technology. A teacher is required to have basic competencies including pedagogic, personality, social, and professional competencies. The basic competencies in question are knowledge, skills, and basic values ​​that are reflected in the habits of thinking and acting as a teacher. Therefore a good teacher is a teacher who is ready for advanced technological developments, especially in education.